Perancangan Sistem Informasi Kegiatan Anggota DPRD Kabupaten Hulu Sungai Tengah Berbasis PHP Dan HTML - Ananda, Nadea Rizky; Hamid, Abdul; Purbiyanto, Eko (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
The Regional People's Legislative Council as a legislative institution has the main activity of accommodating the aspirations of the people as well as containing regulations and laws in the area itself.  The DPRD of Hulu Sungai Tengah Regency while carrying out work activities, the arrangement of the schedule of activities is still printed on paper, this has made DPRD members in Hulu Sungai Tengah Regency difficult to see the schedule of activities, besides that the delivery of information and work programs is only done via social media or the media.  other information, so that people do not absorb the information available at the DPRD office of Hulu Sungai Tengah Regency.  The results of the research conducted are to create an information system that makes it easier for DPRD members of Hulu Sungai Tengah Regency to view activity schedules and make all information transparent which the public can see at any time.  To support this research, data collection methods were carried out by observation, interviews, and literature studies and system development methods using the Waterfall method with modeling using UML, MySql database, and using PHP and HTML.  From this research, a website-based information system was produced that made it easy for DPRD members and the public to view activity schedules and transparent information.